PENGARUH POLA ASUH ORANG TUA DAN KECERDASAN INTRAPERSONAL TERHADAP ADVERSITY QUESTION - Rahmawati, Aslihatul; M. Asep Rahmatullah; Mas’ud, Muhamad (Program Studi Pendidikan Agama Islam Program Pascasarjana Universitas Islam Negeri Sultan Maulana Hasanuddin Banten, 2024)
This research was conducted using a quantitative approach, the number of samples was 68 using a saturated sampling technique. Data collection techniques through observation and questionnaires. The data was processed using SPSS version 26 software so that the results obtained were that there was no positive influence between parenting patterns and the Adversity Quotient with a t-count of -0.764 > 1.671. There is a positive influence between Intrapersonal Intelligence and Adversity Quotient with a tcount of 116,206 > 1.671. There is a simultaneous influence of the Parenting Pattern Variable and the Intrapersonal Intelligence Variable on the Adversity Quotient Variable with a significance value of 0.000 < 0.05.